Multiscale Modeling of the Ventricles: From Cellular Electrophysiology to Body Surface Electrocardiograms - Keller, David Urs Josef (Karlsruhe transactions on biomedical engineering / Ed.: Karlsruhe Institute of Technology / Institute of Biomedical Engineering, 2011)
This work is focused on different aspects within the loop of multiscale modeling:On the cellular level, effects of adrenergic regulation and the Long-QT syndrome have been investigated.On the organ level, a model for the excitation conduction system was developed and the role of electrophysiological heterogeneities was analyzed.On the torso level a dynamic model of a deforming heart was created and the effects of tissue conductivities on the solution of the forward problem were evaluated.